Experimental Study on the Shock Absorption Performance of Combined Aluminium Honeycombs under Impact Loading - Lei Cao; Yuliang Lin; Fangyun Lu; Rong Chen; Zhifeng Zhang; Yan Li (Shock and Vibration)
Shock absorption characteristics of combined aluminium honeycomb structures were studied experimentally. In the experiments, a testing platform was design to compare the shock absorption level of different honeycomb specimens quantitatively. The shock response curves of six test points mounted on the platform were recorded with acceleration sensors when the buffer was impacted by a bullet driven by high pressure gas. The maximum acceleration values in time domain and in specifically spectral domain were obtained based on spectral analysis. Comparing the data of combined aluminium honeycomb buffer and single aluminium honeycomb buffer, conclusion can be obtained that shock absorbing characteristic of combined aluminium honeycomb buffer is better. Furthermore, compression properties of three kinds of buffers were tested under quasi-static state. The energy absorption parameters were calculated. The results show suitable combined aluminium honeycomb buffer can smooth the stress and lower the energy applied to the testing platform.